Determinants of private equity investment in South Africa: an ARDL Bounds Testing Approach - Ngewnya, Noluthando (Graduate School of Business (GSB), 2020)
The private sector in Africa is dominated by micro, small, and medium scale enterprises (MSMEs). This sector of the economy often finds it the most difficult to raise financing from the formal financial institutions. This funding problem is further exacerbated by the fact that financial services sector in the economy is very under developed; hence, there is limited sources of debt financing available to entrepreneurs. Private Equity Funding has played a pivotal role in providing capital to this sector and the African continent would benefit from a buoyant Private Equity market. This study, therefore, seeks to examine the determinants of the Private Equity activity in the South African environment, in order to make recommendations to policy makers as to the policies that they should implement in order to increase Private Equity fund raising activity. This study explores the determinants of Private Equity in South Africa from 2002 to 2016. The autoregressive distributed lag (ARDL) bounds approach to co-integration (M. Hashem Pesaran, Shin, & Smith, 2001) is adopted to determine the relationship between economic, financial, and regulatory variables and growth in Private Equity Funds under management. For economic variables, this study looks at exchange rates, interest rates, GDP growth, the inflation rate, and the level of entrepreneurship in the country. Secondly, for financial variables, it looks at stock market development and the development of the financial sector in the country. Lastly, for regulatory variables, it looks at the effect the tax rate, the political environment, and the regulatory environment has on Private Equity activity. The results of the study found no evidence to support a deterministic relationship between the variables macroeconomic environment, financial development, and the regulatory environment with growth in Private Equity Funds under management in the South African context. The findings of this study can be explained by the opportunistic nature of the Private Equity business. This means that investors look for opportunities in markets where they can make substantial returns, and those opportunities are not necessarily informed by the macroeconomic environment of the countries where the opportunities avail themselves.